Types of experimentation for the training of physics teachers (Memorias Sifored - Encuentros Educación UAN, 2021)
The teaching of physics at school and university level often falls into monotony and boredom for students, the use that has been given to experimentation has not been unrelated to it. In teacher training, our goal is to chart new paths that allow Physics Bachelor students to characterize experimentation as a method of interaction in the classroom, through unconventional treatments, in order to develop thinking skills in their students.
Keywords: physical; classroom experimentation; thinking skills